Reliability of goniometric measurement of navicular position to determine the medial longitudinal arch height among normal adults - DR. D. RAKESH MPT,; AYYAPPAN JAYAVEL MPT, (International Journal of Pharma and Bio Sciences, 2018)
Overuse injuries in the lower extremity are numerous, costly, and represent a large clinical problem. Despite the extent of the problem, there is a paucity of knowledge on the causes of the injuries. The purpose of the study is to modify the original Feiss line test to increase the accuracy of the test and to establish its utility in clinical practice.The study design adopted is observational design and descriptive type. 100 samples were selected with simple random sampling method based on the inclusion criteria. The participant were made to stand in an upright position, toes pointing straight forward, with the right foot behind the left with the left heel and right great toe on the same transverse plane. Pearson correlation co efficient shows Goniometric measurement of navicular position has good inter and intra tester reliability during loading and rest at P=0.05 level (statistically significant).This study concluded that the measurement of navicular position with this method was easy and reliable.